큐브위성 개발프로그램을 통한 우주전문 인력양성 성과 - 차진영(Jinyeong Cha); 오현웅(Hyunong Oh) (항공우주시스템공학회지, 2014)
The CubeSat, which was first launched to verify new technologies and for educational purposes, is now widely used as an educational tool since it makes possible development of manpower through practical training to produce the satellite at low development costs. At present, research and development on the CubSat is rapidly expanding in domestic and foreign universities. As one of the final 3 teams selected in the 2013 CUBE SATELLITE CONTEST organized by the Ministry of Science, ICT and Future Planning, Chosun University is also currently conducting R & D of STEP Cube Lab, which is a CubeSat scheduled to be launched in 2015 and whose main task is to verify space-based technologies in orbit. The present paper tries to present an overview of the CubeSat of Chosun University whose development is being led by its undergraduate students, and further, introduce the strengths of the present development program for developing space experts, based on the educational achievements from the R & D.